A comparison in the ability to detect diabetic retinopathy between fasting plasma glucose and HbA1c levels in a longitudinal study. Issue 1 (4th November 2020) - Matsushita, Yumi; Yokoyama, Tetsuji; Takeda, Norio; Katai, Naotatsu; Yoshida‐Hata, Natsuyo; Nakamura, Yosuke; Yamamoto, Shuichiro; Noda, Mitsuhiko; Mizoue, Tetsuya; Nakagawa, Toru
Abstract: Aims: The relationship between HbA1c and diabetic retinopathy is expected to differ between different races. In this study, we verified which of HbA1c and fasting plasma glucose (FPG) is more effective for detecting the diabetic retinopathy longitudinally in a Japanese population. Materials and Methods: The study subjects underwent health examinations twice (including eye test and questionnaire of lifestyle and health) in 2008‐2009 (baseline) and in 2012‐2013 (4‐year follow‐up). Both non‐DM and DM patients at baseline were included as the participants. Of these participants, who had not been diagnosed with retinopathy at the baseline survey (n = 2427; 2150 men and 277 women) had eye fundus photographs taken four years later (follow‐up survey). The odds ratios of incidence of retinopathy according to the eight groups of FPG and HbA1c were estimated using multiple logistic regression analysis adjusted for sex and age. Receiver operator characteristic analysis was used to evaluate each value associated with the presence or absence of retinopathy. Results: The odds ratios (95% confidence intervals) of incidence of retinopathy by HbA1c level categories, in ascending order, were 1.0 (ref.), 5.66 (1.14‐28.26), 1.69 (0.24‐12.04), 3.03 (0.50‐18.28), 1.04 (0.09‐11.59), 4.73 (0.78‐28.69), 4.12 (0.74‐22.85) and 24.47 (5.61‐106.75). For both FPG and HbA1c levels, the odds ratio for the development of retinopathy increased linearly with the increases in the levels FPG and HbA1c, and no clear threshold was observed. The AUC values (SE) for FPG and HbA1c were almost the same, at 0.750 (0.046) and 0.732 (0.048). Conclusions: It was clarified that the higher the level of FPG and HbA1c was, the higher the incidence of retinopathy after 4 years was. There was no clear threshold. The detection ability of the incidence of retinopathy was almost the same between FPG and HbA1c, suggesting it is possible to detect the risk of retinopathy by HbA1c only. Abstract : A comparison in the ability to detect diabetic retinopathy between fasting plasma glucose and HbA1c levels in a longitudinal study.